2020
DOI: 10.3390/genes11040422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Subcutaneous Adipose Tissue from Local Pig Breeds

Abstract: When compared to modern lean-type breeds, Portuguese local Alentejano (AL) and Bísaro (BI) pig breeds present a high potential for subcutaneous and intramuscular fat (IMF) deposition which contributes for better meat quality. The aim of this work was to explore the genome function to better understand the underlying physiological mechanisms associated with body fat accretion. Dorsal subcutaneous fat samples were collected at slaughter from adult animals (n = 4 for each breed) with~150 kg body weight. Total RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 108 publications
6
22
0
2
Order By: Relevance
“…In Iberian pigs, the ACACA gene was proposed as a candidate gene responsible for intramuscular content of saturated fatty acids and monounsaturated fatty acids fatty acids [ 47 ]. Furthermore, the up-regulation of FASN and SCD genes were reported in Alentejano pigs and related to the higher fat deposition observed in this breed [ 20 ]. The research performed on Iberian × Landrace pig cross lines indicated a significant association of the ACACA gene and IMF palmitic fatty acid percentage [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Iberian pigs, the ACACA gene was proposed as a candidate gene responsible for intramuscular content of saturated fatty acids and monounsaturated fatty acids fatty acids [ 47 ]. Furthermore, the up-regulation of FASN and SCD genes were reported in Alentejano pigs and related to the higher fat deposition observed in this breed [ 20 ]. The research performed on Iberian × Landrace pig cross lines indicated a significant association of the ACACA gene and IMF palmitic fatty acid percentage [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, in pigs, transcriptomic research has been applied to identify the regulation processes determining feed efficiency [ 18 ] and to examine the body’s response to different nutritional treatments [ 19 ]. Processes based on adipocyte tissue gene expression profiling in two Portuguese local pig breeds to determine the fat deposition via controlling of de novo fatty acid synthesis have been proposed, [ 20 ]. Furthermore, gene expression profiling in combination with genome resequencing has allowed for the detection of genes potentially related to backfat thickness [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reads were mapped to a mouse genome (mm10) using the STAR aligner with default setting and differential gene analysis was conducted using DESeq2 in Partek Flow 8.0 software (Partek, USA). Gene expression levels were obtained through the count of total exon reads for statistical analysis 19 . Enrichment analysis of DEGs was performed using Ingenuity Pathway Analysis (IPA®, QIAGEN Redwood City, www.qiagen.com/ingenuity) as described previously 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Fat plays an important part in the life activities of livestock [1], including confronting starvation, lactation and parturition [2,3]. Meanwhile, as the core of the nutritional value of meat, the type and amount of fat are among those key factors which in uence meat quality like appearance, avor and tenderness [4][5][6], and is also essential to protect the carcass during cooling, avoiding cold shortening, drip loss and dark cutting [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%